Reinventing innovation : designing the dual organization - Smith, Aaron, 1972-; Sutherland, Fiona; Gilbert, David H. (Palgrave Macmillan, 2017)
"Based on research findings and detailed, original cases, this book charts the new innovation imperative, where organizations must deliver on dual goals: an efficient return on current operations, and a burgeoning pipeline of new products. It argues that the two pursuits cannot be achieved through a bland compromise, or by switching priorities back and forth. Only a 'dual' organization capable of amplifying the tension can optimize efficiency while seeding innovation. Reinventing Innovation examines the nature of dual organizing, presents a series of in-depth cases to reveal its principles, and explains how to fortify organizations with 'ambidexterity' capabilities"-- Provided by publisher.
Keywords: Technological innovations.; elektronické knihy; electronic books